Implementation of Pursed Lips Breathing Technique on patient with Tuberculosis: Case Study - Salsabila, Salwa; Patimah, Iin (Nursing Case Insight Journal, 2025)
Pulmonary tuberculosis (TB) is a contagious infectious disease caused by Mycobacterium tuberculosis, primarily affecting the lungs but also capable of attacking other organs in the body. A common symptom experienced by TB patients is shortness of breath, increased respiratory rate, and reduced oxygen saturation levels. One nursing intervention that can be applied is the pursed lips breathing technique. This technique involves two main mechanisms: a strong, deep inhalation and an active, prolonged exhalation, with the primary goal of increasing oxygen saturation in the patient’s body. The aim of this case study is to analyze the nursing care provided to a pulmonary tuberculosis patient at the Umar Bin Khatab 1 treatment room, employing the pursed lips breathing technique. The descriptive-analytical method was used in this case study, focusing on nursing assessment, diagnosis, intervention, implementation, and evaluation, following an Evidence-Based Practice (EBP) approach. The results of the case study show that the pursed lips breathing technique effectively alleviated the patient’s shortness of breath, improved breathing frequency, and increased oxygen saturation. The study recommends that the pursed lips breathing technique be used as a nursing intervention for patients with ineffective breathing patterns.